S n ( x ) = r = 1 ∑ n ⌊ r x ⌋
For x ∈ R , define S n ( x ) as above.
Evaluate
⌊ n → ∞ lim n 2 S n ( x ) ∣ ∣ ∣ ∣ x = 2 0 1 5 . 2 0 1 6 2 0 1 7 ⌋ .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
That's a nice proof-based question :)
Since you've provided x = 2015 (an integer), we don't need to think so high like squeeze theorem to calculate the answer. If you provide decimal x like x = 2015.abcdefgh...., the problem wouldn't have been that easy :)
Log in to reply
Thanks for pointing that out. I have edited the problem accordingly.
Very good use of Often neglected Sandwich theorem :)
Sandwich Theorem!
Break the gif into two parts. One is real part and other fractional part. Since fractional part will return a value between zero and one, it's contribution to the limit becomes zero. The question is now reduced to calculate a basic limit, which can be calculated easily using limit as a sum technique.
cosnidering the limit n → ∞ lim n 2 S n ( x ) when x is fixed
then by stolz cesaro n → ∞ lim n 2 S n ( x ) = n → ∞ lim 2 n + 1 S n + 1 ( x ) − S n ( x ) = n → ∞ lim 2 n + 1 [ ( n + 1 ) x ] = 2 x
by squeeze
so [ n → ∞ lim n 2 S n ( x ) ] = [ 2 x ] = 1 0 0 7
Problem Loading...
Note Loading...
Set Loading...
From the definition of the floor function, it follows that y − 1 ≤ ⌊ y ⌋ ≤ y ∀ y ∈ R . Therefore for each term in S n ( x ) we can write, r x − 1 ≤ ⌊ r x ⌋ ≤ r x . Therefore, on summing up all the terms, we get, r = 1 ∑ n ( r x − 1 ) ≤ r = 1 ∑ n ⌊ r x ⌋ ≤ r = 1 ∑ n r x ⇒ 2 n x ( n + 1 ) − n ≤ S n ( x ) ≤ 2 n x ( n + 1 )
Dividing throughout by n 2 and taking the limit we get, n → ∞ lim 2 x ( 1 + n 1 ) − n 1 ≤ n → ∞ lim n 2 S n ( x ) ≤ n → ∞ lim 2 x ( 1 + n 1 ) Realizing that the limit of the lower estimate is same as that of the upper one, we can state the required limit is the equal value by invoking the Squeeze Theorem .
∴ n → ∞ lim n 2 S n ( x ) = 2 x .
Thus the required value is ⌊ 2 2 0 1 5 . 2 0 1 6 2 0 1 7 ⌋ = 1 0 0 7 .
Note:
The actual inequality for the floor function is y − 1 < ⌊ y ⌋ ≤ y . Using the ≤ sign instead of < keeps the essence of inequality intact but makes it easier to relate with the squeeze theorem and hence I have written the inequality with the ≤ sign.